Motives for physical activity in older men and women: A twin study using accelerometer-measured physical activity - Aaltonen S; Waller K; Vaha-Ypyä H; Rinne J; Sievanen H; Silventoinen K; Kaprio J; Kujala UM (WILEY, 2022)
Motives for physical activity may vary considerably by age, sex, and the level of physical activity. We aimed to examine motives for physical activity in older men and women with different physical activity levels as well as whether genetic and/or environmental factors explain those motives. Finnish twins (mean age 72.9 years, 262 full twin pairs) self-reported their motives for physical activity. Time spent on moderate-to-vigorous physical activity was monitored using a hip-worn accelerometer. Comparisons between the different physical activity groups of older twins (n = 764-791/motive dimension) were analyzed using the Wald test, and effect sizes were calculated as Cohen's d. Quantitative genetic modeling was used to estimate genetic and environmental contributions. For both sexes, the most frequently reported motives for physical activity were physical fitness, health maintenance, and psychological well-being. Conforming to others' expectations was more important for men than for women (P < .001, Cohen's d = 0.38), while appearance (P = .001 Cohen's d = -0.24) and psychological well-being (P = .02, Cohen's d = -0.17) were highlighted by women. Most of the motive dimensions differed significantly between the physically active and inactive individuals. It was estimated that 5%-42% of the variation in motives was contributed by genetic factors and 58%-95% by environmental factors. The result that environmental factors contribute in a great deal to motives indicates that interventions to motivate physically inactive older individuals to be physically active can be successful. However, personalized interventions are needed because sex and the level of physical activity were found to be associated with older individuals' motives for physical activity.